Household air pollution and high blood pressure: a secondary analysis of the 2016 Albania demographic health and survey dataset - Abba, MS; Nduka, CU; Anjorin, S; Uthman, OA (MDPI, 2022)
Background: Hypertension is a significant public health problem in low- and middle-income countries (LMICs). This study aimed to examine the association between household air pollution (HAP) and blood pressure using data from the 2016 Albania Demographic Health and Survey (DHS). Methods: We computed the odds ratio (OR) for the prevalence of hypertension between respondents exposed to clean fuels (e.g., electricity, liquid petroleum gas, natural gas, and biogas) and respondents exposed to polluting fuel (e.g., kerosene, coal/lignite, charcoal, wood, straw/shrubs/grass, and animal dung). Result: The results show that participants exposed to household polluting fuels in Albania were 17% more likely to develop hypertension than those not exposed to household air pollution (OR = 1.17, 95% CI 1.10 to 1.24). Subgroup analysis revealed that the odds of hypertension were more significant among women (OR = 1.22, 95% CI 1.13 to 1.31), rural residents (OR = 1.12, 95% CI 1.04 to 1.22), and participants aged >24 years (OR = 1.35, 95% CI 1.12 to 1.62) who were exposed to household polluting fuels compared to their counterparts who were not exposed. In summary, the results of the study show significant associations between household air pollution and hypertension risk overall, especially among women, rural dwellers, and people aged >24 years in Albania. Conclusion: In this study, an association between household air pollution and the risk of hypertension was found, particularly among low-income households, those with no education, women, and those who live in rural areas.